2016
DOI: 10.1016/j.njas.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Explaining production expansion decisions of Dutch dairy farmers

Abstract: The abolition of dairy quotas in Europe in 2015 has been accompanied by uncertainty on expansion of the European dairy sector. Whereas the total amount of quotas was limited and the value of quotas was falling before 2015, a significant part of active Dutch dairy farmers followed an expansion strategy in the recent past. Therefore, it was expected that the overall milk production in the Netherlands will substantially increase after abolishment of the quota. The objective of this study is to analyse which facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 31 publications
1
50
0
1
Order By: Relevance
“…So, the solution considered could be higher milk production and the breeding of more cows rather than diversification of activities and self-valorisation activity, the development of which requires a lot of time. Samson et al (2016) [14] confirmed this in the Netherlands by highlighting a nearly significant effect of labour productivity on the DP increase strategy.…”
Section: Effect Of Past Crisis On Perceptions Of the Ideal Future Farmmentioning
confidence: 66%
See 4 more Smart Citations
“…So, the solution considered could be higher milk production and the breeding of more cows rather than diversification of activities and self-valorisation activity, the development of which requires a lot of time. Samson et al (2016) [14] confirmed this in the Netherlands by highlighting a nearly significant effect of labour productivity on the DP increase strategy.…”
Section: Effect Of Past Crisis On Perceptions Of the Ideal Future Farmmentioning
confidence: 66%
“…better valorisation of quality differentiated milk, other activities on the farm, self valorisation, the LBE model. Samson et al (2016) [14] showed that lower stable capacity varies inversely to a DP increase strategy, which is rather a GBI tendency.…”
Section: Production Factorsmentioning
confidence: 99%
See 3 more Smart Citations